Analisis Kemampuan Siswa SMA Kabupaten Sumba Barat Daya Menyelesaikan Soal Higher Order Thinking Skills (HOTS) dalam Pembelajaran Matematika - Edi Wahyudi; Samuel Rex Making Mulyadi (Jurnal Ilmiah Mandala Education (JIME), 2020)
This research aims to describe the competence of Senior High School students at South West Sumba in doing the high order thinking skills test on math lesson. This research is a survey research with 274 students of eleven SMA/MA in South West Sumba as the samples of research. The instrument used in this research was high order thinking skills test which are divided into 1 analysis test, 1 evaluation test and 1 creating test. The instrument has been tested in terms of construct validation and reliability by doing the instrument testing. The percentage of students who answer correctly on higher order thinking skills at analysis aspect with the ability of problem solving which are understanding the problems, making plans and finding solutions are 85.8%, 68.2% and 65.7%. The percentage of students who answer correctly on evaluation aspect with the ability of problem solving which include understanding the problem, making plans and finding solutions are 61.3%, 13.0% and 24.5%. While the percentage of students who answer correctly on creating aspect with the ability of problem solving that include understanding the problem, making plans and finding solutions are 15.3%, 13.5% and 12%. The average score gained by the students on analysis, evaluation and creating aspect which are converted on score 0-100 are 54, 37 and 34.